Toxicity test of Stenochlaena palustris extract based on kidney histopathology examination - Apriasari, Maharani Laillyza; Sari, Tiara Intan Permata; Firdaus, I Wayan Arya Krishnawan (Dental Journal (Majalah Kedokteran Gigi), 2023)
Background: Kalimantan's people consume Stenochlaena palustris leaf extract as food and for traditional medicine. The bioactive components of Stenochlaena palustris leaf extract are flavonoids, alkaloids, saponins, and tannins. An in vitro study shows that the leaf extract has no toxic effect, so it can be used as an alternative drug in oral health, such as in mouthwashes or topical ulcer drugs. Purpose: This study aims to analyze the toxic effects of Stenochlaena palustris leaf extract based on the bleeding and lesions resulting from necrosis in kidney by using histopathology examination. Methods: The Stenochlaena palustris leaves were extracted using 95% ethanol and then given to male Wistar strain (Rattus norvegicus) with a 2,000, 2,500, and 3,000 mg/kg/body weight two times a day for fourteen days. The kidneys were collected and subjected to histopathology examination. Results: There are higher bleeding and necrosis lesion rates in the 2,500 and 3,000 mg/kg/body weight of Stenochlaena palustris leaves extract group compared to the control and 2,000 mg/kg/body weight of Stenochlaena palustris leaves extract group (p<0.05). Conclusion: Stenochlaena palustris leaf extract showed no toxic effect at doses of 2,000 mg/kg/body weight.